Relationship between Islamic Lifestyle and Mental Health in Pregnant Women : A Cross-Sectional Study - Pakzad, Mona; Dolatian, Mahrokh; Jahangiri, Yahia; Nasiri, Malihe; Zeydi, Amir Emami (Bangladesh Journal of Medical Science, 2020)
Objective: Mental health problems in women during pregnancy are widely associated with the negative consequences of pregnancy. Various factors can affect the mental health improvement in pregnancy. The effects of lifestyle and especially the Islamic lifestyle on mental health are unknown. Therefore, the researcher determined to examine the correlation between the Islamic lifestyle and women’s mental health in pregnancy. Materials and Methods: The study on 300 pregnant women referred to the clinics affiliated to Shahid Beheshti University of Medical Sciences was carried out as descriptive cross-sectional. The research tools included the Islamic lifestyle questionnaire and DASS-21. Results: The results showed that there is a significant negative relationship between mental health and the Islamic lifestyle. (r = -0.310). The regression test results show that the mean score of the mental health problems decreases 0.09 per unit by increasing an Islamic lifestyle score. Conclusion: Since the results show that there is a significant negative relationship between Islamic lifestyle and the women’s mental health, interventional studies are suggested to increase awareness and change lifestyle in order to improve the mental health. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.394-400